2005
DOI: 10.2355/isijinternational.45.876
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Acicular Ferrite from Flux Ingredients in Submerged Arc Weld Metal of C-Mn Steel

Abstract: The prediction model has been developed for low carbon steel weld metal acicular ferrite microstructure as a function of flux ingredients such as CaO, MgO, CaF 2 and Al 2 O 3 in submerged arc welding carried out at fixed welding parameters. The results of quantitative measurements of acicular ferrite (AF) on eighteen no. of weld metal samples were utilised for developing the prediction model. Among the flux ingredients, CaO appears to be most important as an individual as well as interaction with other ingredi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…The quality of weld-metal is often evaluated by many characteristics such as chemical composition, mechanical properties, bead profile and microstructure. Studies have shown that these characteristics are influenced by the welding flux formulation; therefore it is important to select the right type of welding flux ingredients and choose the appropriate proportions of the various flux ingredients to attain a good weld-metal quality [2][3][4][5][6][7][8][9][10] . The conventional approach to welding flux development is by experimental optimization.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The quality of weld-metal is often evaluated by many characteristics such as chemical composition, mechanical properties, bead profile and microstructure. Studies have shown that these characteristics are influenced by the welding flux formulation; therefore it is important to select the right type of welding flux ingredients and choose the appropriate proportions of the various flux ingredients to attain a good weld-metal quality [2][3][4][5][6][7][8][9][10] . The conventional approach to welding flux development is by experimental optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The XVERTD method is a proven approach that is sufficient not only to fit the proposed model but also allows a test of model adequacy from a minimal experimental efforts 14 . Kanjilal and his co-investigators [5][6][7][8] used their experimental data to develop prediction models for the measured responses such as weld-metal composition, mechanical properties, microstructure and element transfer characteristics of the flux. However, they did not use the models to perform optimization on the responses.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations